A chromosome‐level assembly of the black tiger shrimp (Penaeus monodon) genome facilitates the identification of growth‐associated genes. (16th March 2021) - Uengwetwanit, Tanaporn; Pootakham, Wirulda; Nookaew, Intawat; Sonthirod, Chutima; Angthong, Pacharaporn; Sittikankaew, Kanchana; Rungrassamee, Wanilada; Arayamethakorn, Sopacha; Wongsurawat, Thidathip; Jenjaroenpun, Piroon; Sangsrakru, Duangjai; Leelatanawit, Rungnapa; et al.
Abstract: To salvage marine ecosystems from fishery overexploitation, sustainable and efficient aquaculture must be emphasized. The knowledge obtained from available genome sequence of marine organisms has accelerated marine aquaculture in many cases. The black tiger shrimp ( Penaeus monodon ) is one of the most prominent cultured penaeid shrimps (Crustacean) with an average annual global production of half a million tons in the last decade. However, its currently available genome assemblies lack the contiguity and completeness required for accurate genome annotation due to the highly repetitive nature of the genome and technical difficulty in extracting high‐quality, high‐molecular weight DNA. Here, we report the first chromosome‐level whole‐genome assembly of P. monodon . The combination of long‐read Pacific Biosciences (PacBio) and long‐range Chicago and Hi‐C technologies enabled a successful assembly of this first high‐quality genome sequence. The final assembly covered 2.39 Gb (92.3% of the estimated genome size) and contained 44 pseudomolecules, corresponding to the haploid chromosome number. Repetitive elements occupied a substantial portion of the assembly (62.5%), the highest of the figures reported among crustacean species. The availability of this high‐quality genome assembly enabled the identification of genes associated with rapid growth in the black tiger shrimp through the comparison of hepatopancreas transcriptome of slow‐growing and fast‐growing shrimps. The results highlighted several growth‐associated genes. Our high‐quality genome assembly provides an invaluable resource for genetic improvement and breeding penaeid shrimp in aquaculture. The availability of P. monodon genome enables analyses of ecological impact, environment adaptation and evolution, as well as the role of the genome to protect the ecological resources by promoting sustainable shrimp farming.